2005
DOI: 10.1002/path.1719
|View full text |Cite
|
Sign up to set email alerts
|

Location of inclusion cysts in mouse ovaries in relation to age, pregnancy, and total ovulation number: implications for ovarian cancer?

Abstract: Benign ovarian cysts are thought to be precursor lesions that differentiate and transform into carcinoma. With the aim of testing the hypothesis that increased ovulation number increases the frequency or number of ovarian cysts, the development and appearance of ovarian cysts was investigated in mice of differing ages and total lifetime ovulation number. High total ovulation number was induced by keeping mice in cages divided by a screen, with a male on one side and two females on the other side. Significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 37 publications
4
30
1
Order By: Relevance
“…The formation of cysts has been reported previously to be location dependent after chronic ovulation (16). To confirm and extend these previous observations, the location of each cyst was determined as either located in the hilus (this did not include cysts that were on the oviduct side but not physically located within the hilus), perpendicular to the hilus at either edge, opposite the hilus, or in the middle of the ovary (Fig.…”
Section: Superovulation and Cyst Location In Smad2dn Mouse Ovariesmentioning
confidence: 93%
See 1 more Smart Citation
“…The formation of cysts has been reported previously to be location dependent after chronic ovulation (16). To confirm and extend these previous observations, the location of each cyst was determined as either located in the hilus (this did not include cysts that were on the oviduct side but not physically located within the hilus), perpendicular to the hilus at either edge, opposite the hilus, or in the middle of the ovary (Fig.…”
Section: Superovulation and Cyst Location In Smad2dn Mouse Ovariesmentioning
confidence: 93%
“…The wounding and healing process is necessary for oocyte release, but frequent rupture and repair also increases the chance for spontaneously developing mutations to accumulate in cellular DNA (13)(14)(15). Indeed, enhanced cyst formation and epithelial proliferation was observed in incessantly ovulating mice linking the process of ovulation with cyst formation (16,17). In addition, factors that increase ovulation increase the risk of developing ovarian cancers, whereas factors that reduce total lifetime ovulation reduce cancer risk (18 -25).…”
mentioning
confidence: 96%
“…The dissection, fixation, and processing of the ovaries has been described previously, as has estimation of total lifetime ovulation number [1,2]. Female out-bred CD-1/Swiss Webster mice were housed in two groups in a temperature- and light-controlled facility; (1) in breeding pairs (BR group) with one female housed with a male Swiss Webster mouse and (2) in a cage divided by a perforated screen, with two females housed beside, but not in contact with a single male mouse, to induce incessant ovulation (IO group) and prevent breeding [1].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies demonstrated that ovaries of CD-1/Swiss Webster mice subjected to incessant ovulation (IO) had changes suggestive of a precancerous state, such as an increased number of surface invaginations, stratification of the ovarian surface epithelium (OSE) and inclusion cyst formation [1,2]. Dilation of the rete ovarii tubules to form serous inclusion cysts also occurred with age in breeding females with a much lower total ovulation number [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation